2015
DOI: 10.1039/c5sc01811k
|View full text |Cite
|
Sign up to set email alerts
|

Site-selective formation of an iron(iv)–oxo species at the more electron-rich iron atom of heteroleptic μ-nitrido diiron phthalocyanines

Abstract: A combination of MS and computation on μ-nitrido bridged diiron complexes reveals H2O2 binding to the complex and generates an oxidant capable of oxidizing methane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
38
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 76 publications
(45 citation statements)
references
References 111 publications
6
38
1
Order By: Relevance
“…Structurally all geometries look very similar especially regarding the ligand structure, and, for instance, all Pt–CH 3 distances are within 0.007 Å, which implicates a minor effect on the Pt binding properties upon changing the transition metals. Most optimized geometries give bond lengths as expected from calculations on analogous complexes [ 13 , 14 , 15 ]. In the case of A Fe,2CO a full geometry optimization without constraints led to hydrogen atom transfer from Fe to the carbene center, which implies a low-barrier process for hydrogen transfer.…”
Section: Resultssupporting
confidence: 55%
“…Structurally all geometries look very similar especially regarding the ligand structure, and, for instance, all Pt–CH 3 distances are within 0.007 Å, which implicates a minor effect on the Pt binding properties upon changing the transition metals. Most optimized geometries give bond lengths as expected from calculations on analogous complexes [ 13 , 14 , 15 ]. In the case of A Fe,2CO a full geometry optimization without constraints led to hydrogen atom transfer from Fe to the carbene center, which implies a low-barrier process for hydrogen transfer.…”
Section: Resultssupporting
confidence: 55%
“…The corrolazine, in addition to the missing meso-CH group has the other three meso-CH groups replaced by nitrogen atoms. As a consequence, corrole and corrolazine ligands have an overall charge of +3, whereas heme, protoporphyrin IX and phthalocyanine rings only have a charge of +2 [ 79 ].…”
Section: Resultsmentioning
confidence: 99%
“… 217 Under catalytic conditions, they were shown to activate C–H bonds of methane (BDE = 104 kcal/mol) to afford formic acid with total turnover numbers (TTN) up to ∼220. 218 Recent computational studies showed that the activation barriers of [(L)Fe IV =N–Fe IV (L •+ )=O] type intermediates for methane oxidation are over 10 kcal/mol lower than that of a model P450 cpd I. 219 The calculation also suggests that the donor properties of the bridged nitrido group dramatically increased the basicity of the oxo group, which is crucial for the high reactivity of this class of compounds.…”
Section: Key Intermediates Involved In O 2 Activatmentioning
confidence: 99%